Surround Suppression and Recurrent Interactions V1-V2 for Natural Scene Boundary Detection - Díaz-Pernas, Francisco J.; Antón-Rodríguez, Míriam; Torre-Díez, Isabel de la; Martínez-Zarzuela, Mario; González-Ortega, David; Boto-Giralda, Daniel; Díez-Higuera, J. Fernando (IntechOpen, 2011)
None